Bone Fragment Co-transplantation Alongside Bone Marrow Aspirate Infusion Protects Kidney Transplant Recipients - Luo, Xianzhang; Zhang, Ji; Zou, Sijuan; Wang, Xinqiang; Chen, Gen; Li, Zhen; Li, Kaiyan; Wang, Mengqing; Chen, Zhishui; Ming, Changshen; Zhu, Xiaohua; Gong, Nianqiao (Frontiers in Immunology, 2021)
Integration of non-vascularized bone grafting and bone marrow aspirate infusion in transplantation may provide clinical benefit. Here we have incorporated bone fragment co-transplantation and bone marrow aspirate infusion (BF-BM) into living kidney transplantation (LKT). Twenty LKT recipients receiving bone fragments and bone marrow aspirates donated from their corresponding donors were enrolled into a retrospective study. A contemporaneous control group was formed of 38 out of 128 conventional LKT recipients, selected using propensity score matching by a 1:2 Greedy algorithm. Ultrasonography, contrast-enhanced ultrasonography (US/CEUS) and SPECT/CT showed that the co-transplanted bone fragments remained viable for 6 months, subsequently shrank, and finally degenerated 10 months post-transplantation. BF-BM resulted in earlier kidney recovery and more robust long-term kidney function. Throughout 5 years of follow-up, BF-BM had regulatory effects on dendritic cells (DCs), T helper (Th1/Th2) cells and regulatory T cells (Tregs). Both alloantigen-specific lymphocyte proliferation and panel reactive antibody levels were negative in all recipients with or without BF-BM. In addition, the BF-BM group experienced few complications during the 5-year follow-up (as did the donors)—this was not different from the controls. In conclusion, BF-BM is safe and benefits recipients by protecting the kidney and regulating the immune response.